miRNA‑490‑3p promotes the metastatic progression of invasive ductal carcinoma - Lu, Ning; Zhang, Mei; Lu, Lu; Liu, Yan‑Zhao; Zhang, Hai‑Hong; Liu, Xiao‑Dong (Oncology reports, 2021)
MicroRNA (miRNA/mir)‑490‑3p has been defined as a tumor suppressor in different types of cancer, including breast cancer. However, miR‑490‑3p has been shown to function as a tumor suppressor and promoter in a context‑dependent manner in hepatocellular and lung cancer. Contrary to previous studies, the present study revealed that miR‑490‑3p expression was significantly higher in invasive ductal carcinoma (IDC) tissue specimens, the most common form of breast cancer, compared to tumor‑adjacent normal tissue specimens (n=20). Its expression was also higher in the more metastatic breast cancer cell line, MDA‑MB‑231, compared to the non‑metastatic breast cancer cell line, MCF7, and the moderately metastatic breast cancer cell line, MDA‑MB‑468. The expression of miR‑490‑3p was induced following transforming growth factor (TGF)‑β‑induced epithelial‑to‑mesenchymal transition (EMT) in MCF10A cells. Gain‑and loss‑of‑function assays revealed that the expression of miR‑490‑3p regulated the proliferation, colony formation, EMT, migration and invasion in vitro, but not the apoptosis of MDA‑MB‑468 and MDA‑MB‑231 cells. The knockdown of miR‑490‑3p expression in MDA‑MB‑231 cells inhibited experimental metastasis in a tumor xenograft assay. As in lung cancer, miR‑490‑3p was found to target and downregulate the expression of the tumor suppressor RNA binding protein poly r(C) binding protein 1 (PCBP1). PCBP1 protein and miR‑490‑3p expression inversely correlated in patients with ductal carcinoma in situ (DCIS; n=10; no nodal involvement) and IDC (n=10; different stages of metastatic progression) with a significantly higher miR‑490‑3p expression in patients with IDC compared to those with DCIS. The expression of miR‑490‑3p was negatively associated with both overall and disease‑free survival in the patients with breast cancer included in the present study. On the whole, the results confirm a pro‑metastatic role of miR‑490‑3p in IDC, establishing it as a biomarker for disease progression in these patients.